Legal Protection for Consumers Through Halal Certification Mandate of Law Number 33 of 2014 Concerning Guarantees for Halal Products - Ilham Abdi Prawira (Sharia and Law Faculty, 2022)
This article will discuss legal protection for consumers through halal certification efforts as mandated in the JPH Law. By using a juridical-normative approach to examine in depth the legal protection for consumers regarding the implementation of halal certification. After analysis, it can be seen that there is harmony between the JPH Law and the PK Law in terms of legal protection for consumers. The existence of consumer rights that must be fulfilled as stated in the PK Law requires the fulfillment of consumer rights so that legal certainty for consumers can be realized. The right to security and safety as well as the right to obtain correct information is one of the rights guaranteed by law with the existence of halal certification. Through the obligation of product halal certification for business actors, it has a positive impact on consumers so that consumers no longer feel worried about product halal guarantees and consumers can be protected.Artikel ini akan mendiskusikan mengenai perlindungan hukum bagi konsumen melalui upaya sertifikasi halal sebagaimana diamanatkan dalam UU JPH. Dengan menggunakan pendekatan yuridis-normatif untuk menelaah secara mendalam perlindungan hukum bagi konsumen atas pemberlakuan sertifikasi halal. Setelah dilakukan analisis dapat diketahui bahwa adanya keharmonisan antara UU JPH dan UU PK dalam hal perlindungan hukum bagi konsumen. Adanya hak-hak konsumen yang harus dipenuhi sebagaimana tercantum dalam UU PK menghendaki pemenuhan hak-hak konsumen agar kepastian hukum bagi konsumen dapat terwujud. Hak atas keamanan dan keselamatan serta hak untuk mendapatkan informasi yang benar merupakan salah satu hak yang dijamin oleh undang-undang dengan adanya sertifikasi halal. Melalui kewajiban sertifikasi halal produk bagi pelaku usaha memberikan dampak positif bagi konsumen sehingga konsumen tidak lagi merasa khawatir akan jaminan kehalalan produk serta konsumen dapat terlindungi.